Collaborative Stakeholders in Accelerating Economic Recovery Post COVID-19 Pandemic in Jetak Village, Sidoharjo District, Sragen Regency, Central Java - Riska Wirawan; Setyasih Harini; Andri Astuti Itasari (Budapest International Research and Critics University, 2022)
This study aims to find out the collaborative stakeholders in accelerating economic recovery post Coronavirus Disease 2019 (COVID-19) pandemic in Jetak Village, Sidoharjo District, Sragen Regency, Central Java. The method used in this study uses a descriptive qualitative approach design. Data collection was carried out for approximately two months. Data during the research process were obtained from direct observations and interviews, researchers conducted in-depth interviews with stakeholders who were directly involved in accelerating the economic recovery of Coronavirus Disease 2019 (COVID-19) at Jetak Village, Sidoharjo District, Sragen Regency, Central Java. Researchers do not limit the number of available informants, but rely on the information obtained. The information that the researchers dug up was information related to collaborative stakeholders in accelerating economic recovery after the COVID-19 pandemic in Jetak Village. The results of the study show that collaborative stakeholders in accelerating economic recovery after the COVID-19 pandemic in Jetak Village, Sidoharjo District, Sragen Regency, Central Java, which are established between the Regional Government, Health Service, Social Service, Family Welfare Empowerment Team, and Village Government have been going well but are still not optimal.